FAKTOR YANG MEMENGARUHI PERTUMBUHAN PERUSAHAAN, KINERJA KEUANGAN, DAN PEMBIAYAAN EKSTERNAL TERHADAP PENGUNGKAPAN SUKARELA BESERTA IMPLIKASINYA TERHADAP KUALITAS LABA - Cindy, Cindy; Madya, Synthia (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2018)
The purpose of this research is to analyze the impact of growth, financial performance and external financing on voulantary disclosure and the effect of voluntary disclosure on earnings quality. Hypothesis testing is carried out by using linear regression model using data from Indonesia Stock Exchange in 2012-2015. Company growth is measured by book-to-market ratio, financial performance is measured by return on assets, external financing is measured by issue, voluntary disclosure is measured based on voluntary disclosure index, and earnings quality is measured by annual firm-specific absolute value of the residuals (accruals quality). The examiniation of the first model shows company's growth and financial performance has a significant positive effect on voluntary disclosure, while external financing has no effect on voluntary disclosure. The second model shows that voluntary disclosure has a significant positive impact on earnings quality.